MODEL PENGAWASAN PEMBELAJARAN PENDIDIKAN JASMANI DI SD - Yudha M. Saputra (Jurnal Cakrawala Pendidikan, 2011)
Abstract: A Model for the Supervision in the Learning of Physical Education in Elementary School. This study aimed to optimize the functions of principals and supervisors in the improvement of physical education teachers’ performance. It was a research and development study in which the preliminary steps employed the qualitative approach to obtain information on the existing models at present and attempts to develop one. The result of this study showed that the model for the supervision in the learning of physical education significantly affected the performance of physical education teachers in elementary schools. In other words, the model was effective to improve the quality of teachers’ performance and students’ achievement. Keywords: supervision model, performance, physical education